Surgical treatment of type 2 giant mesenteric cyst: case report and literature review - Blaz Zavala, Rogelio A.; García Cerda, Abril E.; Calderon, Uriel Cruz; Elizondo , César Reyes (International Journal of Research in Medical Sciences, 2023)
Mesenteric lesions, including cysts, are rare abdominal tumours and in most cases non-neoplastic. They may have an asymptomatic course or present with pain, abdominal distension or intestinal obstruction. The suggested management is surgical resection of the lesions by laparotomy or minimally invasive surgery. We presented the case of a 48-year-old patient with progressive abdominal distension attributed to liver cirrhosis. Ultrasound and computed tomography of the abdomen showed evidence of a giant cyst of the mesentery with no evidence of tumor activity. We therefore decided to perform an exploratory laparotomy with cystectomy and omentectomy, follow-up and pathology report negative for malignancy.